The potential of thermophilic chitinolytic bacteria Ie Jue, Aceh, Indonesia as larvicide of Helicoverpa armigera (Hübner) - Fitri, Lenni; Anggi, Deby Liestia; Yekki Yasmin, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2022)
This study aims to determine the potential of local isolate thermophilic chitinolytic bacteria as larvicide of Helicoverpa armigera (Hübner). The bacteria that have been isolated from hot springs Ie Jue, Aceh Besar, were then characterized morphologically and tested for their larvicidal potential against the larvae of H. armigera. The parameters observed include the number of chitinolytic bacterial isolates as well as their morphological characteristics, the number of dead larvae, the number of larvae developing into pupae, and morphological characteristics of the larvae before and after the treatment with chitinolytic bacteria. The results of morphological characterization showed that the isolates obtained were seven Gram-positive isolates and four Gram-negative isolates, as well as nine isolates in the form of bacilli, while one isolate of diplococci and diplobasil were each. The highest ability of isolate in causing larval mortality was shown by IBK1, which killed approximately 2.67 (67%) individuals of the larvae, while IBK6 and IBK9 showed the lowest ability in causing larval mortality with average larval mortality of 0.33 (8%) individuals. On the other hand, the number of larvae that are able to develop into pupae is mostly found in IBK 6 and IBK 9, while the fewest are found in IBK 1. After the treatment with the bacteria, the morphology of the larvae body was found to be brown to black, soft, runny, crushed, and smelly. The potential use as larvicides to control H. armigera larvae has been proven in this study that isolated from thermophilic chitinolytic bacteria.